Peran Lembaga PAUD dalam Mencegah Kekerasan pada Anak Usia Dini - Esy Anggraini (Inovasi Pendidikan dan Anak Usia Dini, 2026)
Early Childhood Education (ECE) plays a crucial role in providing safe, comfortable, and child-friendly educational services for young children. However, as the second environment after the family, the potential for violence against children may still occur in ECE institutions if they are not managed optimally. Therefore, efforts to prevent violence against young children need to be implemented comprehensively through a holistic approach that integrates education, caregiving, and early prevention strategies. This study aims to analyze how ECE institutions, such as kindergartens and daycare centers, can function as the first line of defense in detecting, preventing, and addressing various forms of violence, including physical, emotional, and sexual abuse, among children aged 0–6 years. The research method employed is a literature review and policy analysis related to child protection and the implementation of Early Childhood Education. The findings indicate that capacity building through teacher training, the implementation of child protection–sensitive curricula, and strengthened collaboration among schools, families, and communities have proven effective in reducing the risk of violence by up to 40%, based on case studies in Indonesia. The conclusion emphasizes the importance of strengthening regulations, ensuring continuous supervision, and investing in human resource development to reinforce the role of ECE as a key agent in violence prevention and in creating a safe, healthy, and supportive environment for optimal early childhood development.